Correction: Recent developments in the synthesis and applications of chiral ferrocene ligands and organocatalysts in asymmetric catalysis. Issue 46 (24th November 2020) - Cunningham, Laura; Benson, Annette; Guiry, Patrick J.
Abstract : Correction for 'Recent developments in the synthesis and applications of chiral ferrocene ligands and organocatalysts in asymmetric catalysis' by Laura Cunningham et al., Org. Biomol. Chem., 2020, DOI: ; 10.1039/d0ob01933j .